Adaptation management to minimize land fires in peatland hydrological unit Bengkalis Island. Issue 1 (June 2021) - Karmila, Y A; Mizuno, K; Maas, A; Saiya, H G
Abstract: Peatland fires are an annual phenomenon in Bengkalis Island. One of the factors causing peatland fire is wrong land management. Not much research on peatland fires due to land management can provide new evidence that land management models can minimize peatland fires. This study aimed to find a comprehensive management adaptation to minimize land fires on peatland. This study draws on spatial, qualitative, and quantitative data from the literature, project and policy documents, observations from the field, and interviews with key persons and other stakeholders in Peatland Hydrological Unit (PHU) Bengkalis Island. Adaptation of communities around peatland based on sustainable management has a good result in an economic and social aspect. One of the community adaptations to minimize land fires is management without burning. Land management without burning will be beneficial if it is carried out in conjunction with soil amendments such as F1-embio on peat soil that will remain rich in soil fertility bacteria. The result of the study stated adaptive management of communities around peatlands could minimize land fires.